Analisis Kualitas Produk Dan Harga Untuk Meningkatkan Kepuasan Pelaggan Mobil Colt Diesel - Muhammad Awal; Florentina Blandina Parapaga (Musamus Journal of Business & Management, 2021)
This study intends to find out how much influence product quality and price have in increasing customer satisfaction for Colt Diesel Cars in Merauke Regency. The method used is a quantitative method. This study uses multiple regression analysis because it has more than one independent variable, namely product quality and price, while the dependent variable is customer satisfaction. This study used as many as 82 respondents. The data processing of the results of the questionnaire distribution was carried out using SPSS. The results of the tests that have been carried out explain that product quality has a positive and significant effect on customer satisfaction, while price has no effect on customer satisfaction because it does not have a significant value.